A General and Highly Efficient Protocol for the Synthesis of Chalcogenoacetylenes by Copper(I)-Terpyridine Catalyst - Movassagh, Barahman; Yousefi, Ali; Momeni, Badri Zaman; Heydari, Sepideh (Synlett, 2014)
A highly efficient copper-catalyzed Csp–X (X = S, Se, Te) bond-forming reaction of terminal alkynes and diorganyl dichalcogenides has been developed. This transformation was realized through the use of copper(I) iodide as a catalyst, 4′-(4-methoxyphenyl)-2,2′:6′,2′′-terpyridine as a ligand, and K3PO4 as a base. A variety of the functionalized substrates were found to react under these reaction conditions to provide products in good to excellent yields.
Keywords: alkynyl chalcogenides; diorganyl dichalcogenides; terminal alkynes; terpyridines; copper-catalyzed reaction